The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/molecules25112715
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Structural Representation in the Performance of a Deep Neural Network for X-ray Spectroscopy

Abstract: An important consideration when developing a deep neural network (DNN) for the prediction of molecular properties is the representation of the chemical space. Herein we explore the effect of the representation on the performance of our DNN engineered to predict Fe K-edge X-ray absorption near-edge structure (XANES) spectra, and address the question: How important is the choice of representation for the local environment around an arbitrary Fe absorption site? Using two popular representations of chemical space… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
14
1
Order By: Relevance
“…In this Article, we have developed a DNN for the instantaneous prediction of XANES spectra at the Co K-edge, building on our recent work at the Fe K-edge. 46,47 We have demonstrated that our DNN can predict Co K-edge XANES spectra using nothing more than the local geometry of the X-ray absorption site with consistent qualitative accuracy and that it can, in many cases, deliver quantitative (sub-eV) accuracy on peak positions with respect to reference XANES spectra. The structure and performance of the DNN optimised in the present Article is comparable to that reported in our recent work at the Fe K-edge, 46,47 evidencing the potential transferability of our DNN to the K-edges of the other transition metal elements and, eventually, the extension of our model to encompass the rest of the periodic table.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In this Article, we have developed a DNN for the instantaneous prediction of XANES spectra at the Co K-edge, building on our recent work at the Fe K-edge. 46,47 We have demonstrated that our DNN can predict Co K-edge XANES spectra using nothing more than the local geometry of the X-ray absorption site with consistent qualitative accuracy and that it can, in many cases, deliver quantitative (sub-eV) accuracy on peak positions with respect to reference XANES spectra. The structure and performance of the DNN optimised in the present Article is comparable to that reported in our recent work at the Fe K-edge, 46,47 evidencing the potential transferability of our DNN to the K-edges of the other transition metal elements and, eventually, the extension of our model to encompass the rest of the periodic table.…”
Section: Discussionmentioning
confidence: 84%
“…4.5 Â 10 À2 (evaluated against unseen/'out-ofsample' spectra for which the post-edge has been normalised to unity), demonstrating two-fold-improved performance relative to our previous work at the Fe K-edge. 8,46,47 This is due -in partto the larger dataset that we work with here (40 700 local geometry/ spectrum pairs at the Co K-edge vs. 9040 local geometry/spectrum pairs at the Fe K-edge). Fig.…”
Section: Dnn Evaluationmentioning
confidence: 98%
See 1 more Smart Citation
“…Outside of chemistry, ML has been applied in many circumstances including: natural language processing 36–39 ; driverless vehicles 40–44 speech recognition 45–48 ; handwriting analysis 49–51 ; enhancing image resolution 52–55 ; robotics 56–60 ; and, famously, beating the human champions of the games chess 61 and Go 62 . Within chemistry, an incomplete list of applications include: evaluating potential energy surfaces of ground 63–66 and excited states 67,68 ; forming solutions to the Schrödinger equation 69,70 ; modeling molecular wavefunctions 71,72 ; accelerating TS optimization 73,74 ; finding exchange‐correlation functionals for DFT 75,76 ; predicting reaction rate constants 77,78 ; predicting the outcomes of organic reactions 79–84 ; X‐ray, 85–87 UV–Vis, 88 IR, 89–92 and NMR 93–95 spectroscopies; sequence‐based biomolecular function prediction 96,97 and predictions of protein structures 98–101 . Another very recent and exciting application of ML in chemistry is the prediction of activation energies.…”
Section: Introductionmentioning
confidence: 99%
“…a "fingerprint" window sensitive to a particular property or observable) and developing a machine learning model to predict directly the resonances within this window; 48,49,[98][99][100][101][102][103] ii) representing the resonances via a Hamiltonian matrix associated with a closed set of secular equations and developing a machine learning model to predict the Hamiltonian matrix elements; 27,39,41,42,50 and iii) developing a machine learning model to predict directly the spectral lineshapes. [71][72][73][74]104,105 The latter approach, which we adopt in this Article and elsewhere where we have worked with machine learning models for XAS in theoretical 71 and practical 73,74 settings, circumvents the formidable challenge of predicting the huge number of resonances around the Xray absorption edge. 106 Sitting alongside the well-developed theory for XAS (e.g.…”
Section: Introductionmentioning
confidence: 99%